Effects of Inoculation in Gray Cast Iron with the Addition of Niobium from Scrap - Henrique Silva; Orestes Alarcon; João Carlos Espíndola Ferreira (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
Casting is one of the oldest and most widely used manufacturing processes in industry; however, it is known for its high consumption of natural resources and the generation of waste and pollutants. Given the growing need for sustainable practices, this work proposes the reuse of metallic materials through the casting of gray cast iron ingots, using recycled scrap with the addition of niobium from a FeSiNb alloy. The inoculation technique was applied to investigate the influence of niobium on the microstructure and mechanical properties of the cast material. Metallographic and machining tests were carried out to evaluate the quality of the recycled material. The results indicate significant potential in using recycled materials combined with alloying elements such as niobium to improve metallurgical performance and reduce the environmental impact of casting production.